2022
DOI: 10.3390/jcm11133831
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Surgical Intervention for Pediatric Acute Rhinosinusitis with Periorbital Infection

Abstract: Background: Medical versus surgical management of pediatric periorbital infection secondary to acute bacterial rhinosinusitis (ABRS) can be a dilemma for clinicians. This study aimed to evaluate the prognostic factors related to the need for surgical drainage and to help direct management decisions. Methods: Children admitted for periorbital infection secondary to ABRS between 2001 and 2019 were retrospectively reviewed. Demographics, clinical presentations, laboratory data, comorbidities, and computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…21 Type 2 inflammation tends to involve the central part of the sinonasal area, including the nasal septum, olfactory cleft, middle turbinates, and ethmoid cells. 31,32 The mechanism responsible for the predominance of ethmoid sinus inflammation in patients with type 2 CRS remains unclear. One possible explanation is that there are regional differences in the expression patterns of type 2 eosinophilic inflammatory molecules in the nasal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…21 Type 2 inflammation tends to involve the central part of the sinonasal area, including the nasal septum, olfactory cleft, middle turbinates, and ethmoid cells. 31,32 The mechanism responsible for the predominance of ethmoid sinus inflammation in patients with type 2 CRS remains unclear. One possible explanation is that there are regional differences in the expression patterns of type 2 eosinophilic inflammatory molecules in the nasal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…This series found that half of patients with COVID-19 and complicated acute sinusitis ultimately required surgical intervention, despite early initiation of antibiotic regimens. This represents an increased need for surgery as opposed to pediatric patients with complicated acute sinusitis before the start of the COVID-19 pandemic [12] . In these cases, COVID-19 precautions may have delayed surgical intervention that was ultimately necessary to manage the patients' complicated sinusitis.…”
Section: Discussionmentioning
confidence: 99%